School-related victimizations among adolescents: An analysis of National Crime Survey (NCS) narratives - Garofalo, James (Journal of quantitative criminology, 1987)
This paper uses a heretofore untapped source of information in the National Crime Survey (NCS) victimization data—the interviewer narratives—to explore school-related victimizations among adolescents. These narrative reports provide important information bearing on lifestyle and routine activity theories of victimization that is simply not available from the more familiar, highly structured portions of the NCS questionnaire. The NCS narratives suggest that a large proportion of school-related victimizations stems from peer interactions that occur in the course of routine daily activities and escalate into victimizations. Students represent pools of both potential offenders and potential victims who come in frequent contact with each other, often in the absence of capable guardians. However, rather than predatory, calculated attempts to harm, school-related victimizations among adolescents appear to consist primarily of bullying, injured pride, and misguided mischief. The theoretical and methodological implications of this study are highlighted.